The Effect of the Combination of Bay Leaf Extract (Syzygium Polyanthum (Wight) Walp.) And Lemongrass Leaf (Cymbopogon Nardus L. Rendle) On Total Cholesterol Levels in Hyperlipidemic Male White Rats - Muhammad Gunawan; Siti Aisyah Tanjung; Enny Fitriani (Proceeding of the International Conference on Health Sciences and Nursing, 2026)
A study was conducted to evaluate the effect of the combination of bay leaf extract (Syzygium polyanthum (Wight) Walp.) and lemongrass leaf extract (Cymbopogon nardus L. Rendle) on total cholesterol levels in male white rats induced with 80% quail egg yolk and 2% propylthiouracil for 15 days. The combination extracts were administered orally at various doses as follows:Test I: bay leaf extract 350 mg/kg BW and lemongrass extract 200 mg/kg BW; Test II: bay leaf extract 350 mg/kg BW and lemongrass extract 400 mg/kg BW; Test III: bay leaf extract 700 mg/kg BW and lemongrass extract 200 mg/kg BW; Test IV: bay leaf extract 700 mg/kg BW and lemongrass extract 400 mg/kg BW. A 0.5% CMC suspension was used as the negative control, while simvastatin suspension at a concentration of .025% was used as the positive control. The Kruskal–Wallis test showed a significant result (p = 0.02), indicating that the combination of bay leaf and lemongrass extracts significantly reduced total cholesterol levels in hyperlipidemic white rats. The results demonstrated that the combination dose of bay leaf extract 700 mg/kg BW and lemongrass extract 400 mg/kg BW produced cholesterol-lowering effects comparable to simvastatin at a dose of 25 mg/200 g BW (p > 0.05). In conclusion, the combination of bay leaf and lemongrass extracts effectively reduced cholesterol levels in hyperlipidemic white rats.